Common Fiscal Policy - Gabriel Mursa (CES Working Papers, 2014)
The purpose of this article is to demonstrate that a common fiscal policy, designed to support the euro currency, has some significant drawbacks. The greatest danger is the possibility of leveling the tax burden in all countries. This leveling of the tax is to the disadvantage of countries in Eastern Europe, in principle, countries poorly endowed with capital, that use a lax fiscal policy (Romania, Bulgaria, etc.) to attract foreign investment from rich countries of the European Union. In addition, common fiscal policy can lead to a higher degree of centralization of budgetary expenditures in the European Union.
Keywords: F36; E62; 330; common fiscal policy; foreign investment; taxes; public expenditure Romania